Improving hydration of care home residents by increasing choice and opportunity to drink: A quality improvement study. Issue 4 (August 2019) - Wilson, Jennie; Bak, Aggie; Tingle, Alison; Greene, Carolynn; Tsiami, Amalia; Canning, Deebs; Myron, Rowan; Loveday, Heather
Summary: Background & aims: Dehydration is recognised as an important problem among care home residents and can be associated with severe consequences. Insufficient provision of fluids to meet resident preferences and lack of assistance to drink have been identified as key factors driving under-hydration of care home residents. Using targeted interventions, this study aimed to optimise hydration care for frail older people in a care home setting. Methods: The study used quality improvement methods to develop and test interventions to extend drinking opportunities and choice in two care homes. Changes were made and evaluated using Plan-Do-Study-Act (PDSA) cycles. Data were captured on the amount of fluids served and consumed, and staff and resident feedback. The long-term impact of the interventions was assessed by measuring daily laxative and antibiotic consumption, weekly incidence of adverse health events, and average fluid intake of a random sample of six residents captured monthly. Results: The interventions were associated with an increase in the amount and range of fluids consumed, in one home mean fluid intakes exceeded 1500 ml for three consecutive months. Laxative use decreased significantly in both homes. A number of practical and organisational barriers affected the sustainability of interventions. Conclusions: Interventions to optimise the hydration of care home residents can be effective. Plan-Do-Study-Act cycles provide an effective methodology to implement new interventions into existing practice in care homes. Sustainable change requires strong leadership, organisational support and teamwork.